Resistin as a Prooxidant Factor and Predictor of Endothelium Damage in Patients with Mild Acute Pancreatitis Exposed to Tobacco Smoke Xenobiotics - Milena Ściskalska; Grzegorz Marek; Zygmunt Grzebieniak; Halina Milnerowicz (Hindawi Limited, 2017)
Objectives. The study was aimed to assess the influence of tobacco smoke exposure on the intensity of inflammation measured by IL-6, α1-antitripsin (AAT) and α1-acid glycoprotein (AGP) concentrations, and Cd level and oxidative stress intensity measured by advanced oxidation protein product (AOPP) concentration in the blood of healthy subjects and AP patients during hospitalization. Endothelin-1 (ET-1) and resistin concentrations, markers of endothelium injury, were determined. Results. An increased IL-6 concentration in healthy smokers compared to nonsmokers and AP patients compared to controls was shown. An increased AAT and AGP concentrations during hospitalization of AP patients were noted, in both smokers (AAT, AGP) and nonsmokers (AAT). In comparison to control groups, in AP patients, a 2-fold increased resistin concentration correlating with ET-1 concentration and decreased albumin concentration accompanied by increased AOPP concentration were demonstrated. AOPP concentration was higher in smokers with AP compared to nonsmokers and gradually enhanced during their hospitalization. Conclusions. Tobacco smoke exposure can have a proinflammatory effect in both healthy subjects and AP patients. Increased resistin concentration in AP patients negatively correlating with albumin concentration has prooxidative effect on this protein resulting in enhanced AOPP level. Increased resistin concentration can intensify AAT and AGP production during AP.